Awareness and Practices of Patients Regarding Oral Hygiene Visiting Dental OPD Sharif Medical and Dental College, Lahore - Aqib Sohail, Aneela Amjad, Maria Jabbar, Mehwish Munawar, Amna Nauman, Nighat Zahid, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Oral cavity related disorders are a serious public health issue because they have a direct influence on the person’s quality of life and add load to healthcare setup. The current study was done to assess the oral hygiene knowledge and routine followed by the habitants of Lahore city. Aim: To assess the oral health awareness, and practices in patients coming dental OPD Sharif Medical and Dental College, Lahore Methodology: This study was conducted among participants coming dental OPD of Sharif Medical and Dental College, Lahore from March to August 2021. A questionnaire was given to all visited patients. The patients from both rural as well as urban background were selected. Results: The outcomes of the study revealed 35% people brush their teeth and 15% use miswak for cleaning, 5% use charcoal while 40% are not bothered about oral hygiene and hence do not clean their teeth at all. Majority of the subjects (80%) go to the dentist in case any dental issue occurs. Conclusion: There is absence of oral health awareness, inadequate knowledge of oral cleanliness practices and their outcome on general wellbeing. There is an imperative necessity for elaborated awareness plans to encourage healthy oral health among general population.